Costal lagoons - Isla, Federico Ignacio (2006)
In recent years, coastal lagoons have received more attention and concern in regard to their increasing use for transportation, recreation and food production (aquaculture). They originated mainly along lowlands in response to the decrease in postglacial sealevel rise (or its fluctuation) and/or heavy longshore drift. They occur in every tidal regime (micro to macrotidal) and climatic regions (low latitudes to high latitudes). There are environments related to them such as tidal inlets and tidal deltas that control their present evolution. There have been many alterations of coastal lagoons; they are induced by dredging, eutrophication, pollution, hydrological imbalances and ecosystem modifications due to overfishing, introduction of species, or aquaculture.